PHYSIOLOGICAL SUBSTANTIATION FOR THE CHOICE OF THE START FORMULAS TO FEED A TERM INFANT, IF THERE ARE CONTRAINDICATIONS TO THE BREAST FEEDING - N.M. Bogdanova; E.M. Bulatova ("Paediatrician" Publishers LLC, 2007)
The lecture give substantiation for the choice of the quality characteristics of the milk formula contents for feeding term infants for the period of the neonatal adaptation to the conditions of the extrauterine life. The physiological premise for choosing the formula is based on the colostrum contents, which is «the gold standard» for newborn feeding. The authors provide the comparative characteristics and match the contents of the mature milk, colostrum and a number of the start milk formulas. Key words: newborn child, feeding, colostrum, breast milk, milk formula, start formula, prebiotics, probiotics, micro-biocenosis.